Direct Visualization of a Mechanochemically Induced Molecular Rearrangement. Issue 32 (3rd June 2020) - Ardila‐Fierro, Karen J.; Lukin, Stipe; Etter, Martin; Užarević, Krunoslav; Halasz, Ivan; Bolm, Carsten; Hernández, José G.
Abstract: Recent progress in the field of mechanochemistry has expanded the discovery of mechanically induced chemical transformations to several areas of science. However, a general fundamental understanding of how mechanochemical reactions by ball milling occur has remained unreached. For this, we have now implemented in situ monitoring of a mechanochemically induced molecular rearrangement by synchrotron X‐ray powder diffraction, Raman spectroscopy, and real‐time temperature sensing. The results of this study demonstrate that molecular rearrangements can be accomplished in the solid state by ball milling and how in situ monitoring techniques enable the visualization of changes occurring at the exact instant of a molecular migration. The mechanochemical benzil–benzilic acid rearrangement is the focal point of the study. Abstract : Forcing a rearrangement : In situ monitoring of the mechanochemical [1, 2]‐intramolecular phenyl migration in benzil was accomplished by a combination of real‐time analytical techniques and temperature sensing. The mechanochemical rearrangement occurs suddenly after an induction time, without detectable intermediates.